Barriers and Facilitators to Evidence-Based Nursing in Colombia: Perspectives of Nurse Educators, Nurse Researchers and Graduate Students - Rebecca R. DeBruyn; Sandra Catalina Ochoa-Marín; Sonia Semenic (Universidad de Antioquia, 2014)
Objective. To identify and describe the perceptions of nursing researchers, educators, and graduate students regarding the barriers to, and facilitators for, EBN in Medellín, Colombia. Methodology. Using a qualitative descriptive design, in-depth semi-structured interviews were conducted with 12 participants associated with a large university faculty of nursing in Medellín, and one member of the National Association of Nurses. Qualitative content analysis was used to analyze the interview transcripts. Results. Several barriers to EBN were reported, including: lack of recognition of nursing as an autonomous profession; a lack of incentives for nurses to pursue advanced education or engage in research; limited availability and utility of nursing evidence; and a lack of communication between academic and clinical practice environments. Perceived facilitators included an increase in nurses pursuing advanced education opportunities; the current healthcare accreditation process; access to international research and research collaborations; and clinical and research partnerships between universities and clinical institutions. Conclusion. Effective implementation of evidence-based nursing practices is a necessity to translate the vast amount of health-related research, knowledge, and experience into positive changes in healthcare quality.